Assessment of Morphological and Tropane Alkaloids Diversity among some Henbane (Hyoscyamus niger L.) Populations - M Ghorbanpour; H Salehi-arjmand; M Hatami; N Hosseini (Institue of Medicinal Plants, ACECR, 2019)
Background: Black henbane with the scientific name of Hyoscyamus niger which has a wide geographic distribution, is considered as one the most important species for tropane alkaloids extraction. Objective: In this research, morphological and tropane alkaloids variations were assessed within different population of H. niger in their natural habitats. Methods: Totally, 56 individuals were collected from 7 populations of 7 different provinces in Iran, and subsequently morphological and metabolic variations were performed. Alkaloid extraction was carried out using various solvent based on specific procedure. The isolated alkaloids were further characterized using gas chromatography apparatus to detect the type of alkaloids. Results: Results showed that the studied populations were significantly varied according to the all measured traits. The highest leaf dry weight, stem, shoot, whole plant and the number of leaf per plant was related to Guilan population. However, the highest (61.29 cm) and the lowest (16.96 cm) plant height, and maximum (16.13) and minimum (5.75) number of lateral branches were observed in Zanjan and Qom populations, respectively. The hyoscyamine content was varied ranging from 0.1888 g/plant (in Zanjan population) to 0.916 g/plant (in Qom population) with average of 0.5 g/plant. The maximum and minimum ratio of scopolamine to hyoscyamine was obtained in Zanjan (1.80) and Qom (0.049) populations, respectively. Moreover, there was a significant and negative correlation (-0.50**) between hyoscyamine content and plant height. Conclusion: In this research, results of cluster and biplot analyses confirmed a wide variability in morphological and metabolites traits between and within H. niger populations of different studied regions.